Evaluation of the Quality Satisfaction the MELISA Information System with the WebQual 4.0 Method - Revinindia Oktaimanuella; Arista Pratama; Asif Faroqi (Komunitas Dosen Indonesia, 2025)
The integration of information technology in higher education is essential to support academic and administrative activities. The MELISA Information System at Surabaya State University plays a vital role in meeting student needs. Periodic evaluation of user satisfaction is necessary to ensure the quality and effectiveness of the service, as poor system quality can hinder learning and productivity. This study aims to analyze and evaluate the quality of the MELISA Information System at Surabaya State University and its impact on student satisfaction. Specifically, this research seeks to determine how WebQual 4.0's Usability Quality, Information Quality, and Service Interaction Quality dimensions influence user satisfaction. Using a quantitative descriptive survey method, data was collected via online questionnaires from Surabaya State University students who use MELISA. System quality was measured using three dimensions of WebQual 4.0: Usability Quality, Information Quality, and Service Interaction Quality. Data analysis involved descriptive statistics and multiple linear regression to test the effect of quality dimensions on student satisfaction. The results show that Usability Quality, Information Quality, and Service Interaction Quality significantly affect student satisfaction with MELISA. The majority of respondents gave a positive assessment, although some improvements are still needed. Information Quality was found to be the most dominant influence on student satisfaction. The quality of the MELISA Information System, based on WebQual 4.0, is crucial for student satisfaction at Surabaya State University. To increase user satisfaction, the university must continue to improve the usability, accuracy of information, and quality of service interactions in the MELISA system.